Cloud Radiative Forcing of the Diurnal Cycle Climate of the Canadian Prairies - Betts , Alan K.; Desjardins , Raymond; Worth, Devon (Emerging Issues in Environment, Geography and Earth Science Vol. 4, 2023)
This analysis uses 40 years of hourly observations of temperature (T), relative humidity (RH), and opaque cloud cover from 14 climate stations across the Canadian Prairies to analyze the diurnal cycle climate, represented by the mean T and RH and their diurnal ranges. From April to October, when incoming shortwave radiation dominates over longwave cooling, maximum temperature and the diurnal ranges of T and RH increase with decreasing opaque cloud cover, while minimum temperature is almost independent of cloud. During the winter period, both maximum and minimum temperatures fall with decreasing cloud, as longwave cooling dominates over the net shortwave flux, which is reduced by the high solar zenith angle and surface reflection by snow. We relate the daily mean opaque cloud cover to the longwave and shortwave cloud forcing and the effective cloud albedo, using multiyear measurements of downward shortwave and longwave fluxes, and longwave fluxes under clear skies from historical weather reanalysis. We provide quadratic fits to compute effective cloud albedo and net longwave fluxes from opaque cloud cover. During the warm season, the daytime rise of temperature is related to the net radiation, and the nighttime fall is related to the net longwave cooling. The diurnal range of T, RH, and all the net radiative fluxes have a quasi-linear dependence on the effective cloud albedo. This gives a seasonal climate perspective on the coupled land-surface system of T, RH, and cloud cover over the Canadian Prairies, and the winter transitions in snowy climates.